EFFECTS OF TRYPANOSOMA BRUCEI BRUCEI INFECTION ON HAEMATOLOGICAL PROFILE, TESTOSTERONE LEVEL, AND OXIDATIVE STRESS STATUS IN WISTAR RAT (RATTUS NORVEGICUS) - Ademola ADEYEMI, Nasiru; Adamu WADA, Yunusa; Joshua ONIYE, Sonnie; HUSSAINI, Muhammad; Dundere MUHAMMAD, Abubakar (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
Trypanosoma brucei brucei is associated with a number of disease conditions in cattle which has caused a huge loss to the agricultural sector. In this study, male Wistar rats were experimentally infected with T. b. brucei to observe changes in haematological profiles, serum testosterone level, and oxidative stress in the testicles. Group I was not infected, group II and III were infected intraperitoneally with 0.75 x106 and 1.0 x 106 doses of T. b. brucei respectively. Mean PCV, RBC, Hb, and MCV of group II and III decreased progressively, culminating in anaemia when compared with the control group. However, there was a significant (p<0.05) increase in total leucocyte count of group II and III. The testosterone level evaluated in serum using Enzyme-Linked Immunosorbent Assay showed a significant decrease from group II to III. Still, the control group had the highest level of serum testosterone. Biomarkers of oxidative stress, such as Malondialdehyde (MDA), significantly increased in the infected groups. At the same time, reduced Glutathione (GSH), Catalase (CAT) and Superoxide dismutase (SOD) activities were statistically reduced in the testicles of experimental animals. The result suggests that oxidative stress in testicles may be related to the pathology in the testes of rats infected with the parasite.